Epigenetic modulation with the CRISPR/dCas9 system Induction of DNA methylation with the effector domain dnmt3a3L fused to the dCas9 protein - Björkman, Agnes Torell (My University, 2019)
Epigenetics play a crucial role in development, cell differentiation and molecular cell stability, and aberrations in the epigenetic pattern can result in diseases such as cancer. Thus, epigenetic mechanisms are important to study, and methods for modulating the epigenetic pattern are central for this area of research. One epigenetic modification is DNA methylation, which is regulated by the enzyme family of DNA methyltransferases. This thesis presents the first part of method development project using the CRISPR/dCas9 system to induce methylation in the MGMT promoter in primary patient-derived cancer stem cells. We first evaluated a two-vector based system with the sgRNA scaffold and the dCas9 protein on separate plasmids. Transfected cells showed low viability and the plasmid needed to be purified thoroughly in order to achieve high cell viability. However, the PKG promoter, which was first used in the CRISPR/dCas9 system, showed inefficient expression in the investigated cells. The CMV promoter on the other hand showed efficient expression. For further studies, a new one-based vector system was designed where dCas9 and the selective marker are expressed under the CMV promoter.
Keywords: Cellbiologi; Cell- och molekylärbiologi; Medicinsk bioteknologi (med inriktning mot cellbiologi); Livsvetenskaper; Cell Biology; Cell and Molecular Biology; Medical Biotechnology (with a focus on Cell Biology); Life Science